Phylogeny and taxonomic revision of the spider mite genera Aponychus, Paraponychus and Stylophoronychus using morphology (Acari:Tetranychidae) - Hernandes, Fabio A. [UNESP]; Feres, Reinaldo J. F. [UNESP] (CSIRO Publishing, 2013)
Despite their great importance as pests of cultivated plants worldwide, members of the family Tetranychidae have never been subjected to a thorough cladistic analysis to reveal the history and relationships among related genera. Herein, we provide the first phylogenetic analysis and taxonomic review of species of the genera Aponychus, Paraponychus and Stylophoronychus using morphological characters. The results indicate a monophyletic clade uniting the aforementioned genera, although none of the three genera were recovered as monophyletic. We reinstate the tribe Aponychini as the taxon containing those three genera. Aponychus bambusae and A. aequilibris are herein considered junior synonyms of Stylophoronychus vannus and A. corpuzae, respectively. © 2013 CSIRO.
Keywords: cladistics; life history; mite; morphology; phylogeny; spider; taxonomy